Lessons of the financial crisis for future regulation of financial institutions and markets and for liquidity management (IMF [Washington]US, 2009)
Seeks to draw lessons for financial sector regulation and supervision and central bank liquidity management from the ongoing crisis. Focuses principally on implications for the future rather than on immediate crisis management policies.
Keywords: ECONOMIC RECESSION